THE EFFECT OF GIVING GIBBERELLIN ON THE GROWTH AND YIELD OF CHERRY TOMATOES (Lycopersicon esculentum var. cerasiforme) IN VARIOUS OF PLANTING MEDIA WITH SUBSTRATE HYDROPONIC SYSTEMS - Mochammad Febrianto; Supono Budi Sutoto; Suwardi Suwardi (Jurnal Agrivet, 2019)
The efforts to increase cherry tomatoes production can be done by increasing the forming of ovaries. This effort can be helped by utilizing Zat Pengatur Tumbuh (ZPT) or Plant Growth Regulators. The Gibberellin is a growth regulator which has the function of flowering initiation and preventing the flowers from falling off. In addition to PGR, planting media is important for the growth of each plant. The planting media also has function as the root container, and the media which can absorb nutrient solution when it is doused or dripped. This research was conducted at The Greenhouse, Sukun Street, Karangbendo, Jaranan, Banguntapan, Bantul, Daerah Istimewa Yogyakarta. The study was conducted in May to August 2018. The experiment method uses polybag with Split Plot Design. In this experiment, there are two factors, and it repeated three times. The first factor as the main plot is the Plant Growth Regulators concentration of Gibberellin GA3 with the level (G0 : 0 ppm, G1 : 50 ppm, G2 : 75 ppm, G3 100 ppm). The second factor as the sub-plot is the type of planting media (M1: Husk Charcoal, M2: Malang Sand, M3: Husk Charcoal + Cocopeat (1:1)). The observation data is analyzed for its diversity at level of 5%. To find out the differences between the treatments, the method which is used is Duncan Multiple Range Test (DMRT) at level of 5%. The result shows that there is a significant effect of Gibberellin Plant Growth Regulators utilizing and types of planting media to the growth and yield of cherry tomatoes. The best Gibberellin concentration is 100 ppm, and the best media is the Husk Charcoal + Cocopeat (1:1).in the last 45 days. The second factor as a sub plot is browning prevention agents, named thidiazuron, activated charcoal, and vitamin C. Each combination of treatments was repeated 3 times. The result showed that there was the best combinations of treatments that is all combination of lighting and vitamin C 0,88 mg / l in terms of browning. The first 45 days lighting treatment gave the best result on the percentage of life, plantlet height, number of shoots, number of leaves, root length, and fresh weight. The treatment of vitamin C 0.88 mg / l gave the best result on the percentage of life, plantlet height, number of shoots, root length, number of roots, fresh weight, and dry weight.Keyword: Gherry tomatoes, substrate hydroponic, gibberellin, planting media.